Many Genes—One Disease? Genetics of Nephronophthisis (NPHP) and NPHP-Associated Disorders - Srivastava, Shalabh; Molinari, Elisa; Raman, Shreya; Sayer, John A. (Frontiers in Pediatrics, 2018)
Nephronophthisis (NPHP) is a renal ciliopathy and an autosomal recessive cause of cystic kidney disease, renal fibrosis and end stage renal failure, affecting children and young adults. Molecular genetic studies have identified more than 20 genes underlying this disorder, whose protein products are all related to cilia, centrosome or mitotic spindle function. In around 20% of cases there are additional features of a ciliopathy syndrome, including retinal defects, liver fibrosis, skeletal abnormalities and brain developmental disorders. Alongside gene identification has arisen molecular mechanistic insights into the disease pathogenesis. The genetic causes of NPHP are discussed in terms of how they help us to define treatable disease pathways including the cAMP pathway, the MTOR pathway, Hedgehog signalling pathways and DNA damage response pathways. Whilst the underlying pathology of the many types of NPHP remains similar, the defined disease mechanisms are diverse and a personalised medicine approach for therapy in NPHP patients is likely to be required.